Effect Of Die’s Shape, Sheet Thickness and Type of Alloy on the Springback Phenomenon - Bushra Rasheed Mohameed; Ethar Mohamed Mhdi Mubarak; Nawal H. Alsalihi (Engineering and Technology Journal, 2012)
In this paper the effect of the springback on the bending operation of different materials and alloys have been studied. Dies were designed and constructed in different shape ( U-die , V-die) for several sheet’s thickness. Two types of alloys were used; Aluminum Alloy 7020 T6 and Brass Alloy. These alloys have different sheet thickness (2, 4, 6 and 8) mm. Aluminum alloys are heated to 270 °C and 330°C with cooling in the furnace for 90 min. while the brass alloys heated to 300, 320, 340 and 420 °C with cooling for 2 hours in furnace. Bending was done by using the press of 80 ton. The springback is calculated by published equation. It can be concluded that, the springback phenomenon caused to enlarge the external dimensions when releasing the load and thick material have less springback due to the enlarge of the plastic deformation. It’s found that the die’s shapes have great effect on the springback, and when the temperature of the specimen is increased, caused decreased in the springback.